Experimental study and thermodynamic calculation of Lu2O3-SiO2 binary system - 叶信宇 罗洋 刘松彬 吴迪 侯得健 杨凤丽 (Journal of rare earths, 2017)
As a binary system of BaO-Lu_2O_3-SiO_2 ternary system, Lu_2O_3-SiO_2 system was optimized and calculated by CALPHAD approach based on available phase diagram and relevant thermodynamic data of RE_2O_3-SiO_2（RE=Lu,Yb,Y） binary systems as well as our experimental data of Lu_2O_3-SiO_2 system obtained by quenching experiment. The Gibbs free energy of high temperature solution was described by an ionic two-sublattice model as（Lu~（3＋））P（O~（2-）, SiO_2~0）Q. The calculated phase diagram below 1873 K was in good agreement with experimental data at 1573, 1773 and 1873 K. The calculated Gibbs energies of two intermediate phases Lu_2SiO_5 and Lu_2Si_2O_7, the activity of Lu_2O_3 and SiO_2 and specific heat capacities of intermediate phases agreed well with experimental results of Y_2O_3-SiO_2 system. This tentative study will offer help for the research of single-phase phosphor and related metallurgical slags, refractories, high-temperature superconductivity material systems.